Utilization Patterns of Korean Medicine in Hospitalized Stroke Patients in a Collaborative Rehabilitation Setting: A 10-Year EMR-Based Retrospective Study - Soyeon Yu; Eunji Go; Jungsup Lee; Chihyoung Son; Go Eun Lee; Sung Min Lim (Journal of Korean Medicine, 2026)
Objectives: This study aimed to characterize the utilization patterns and collaborative care of Korean medicine (KM) in inpatient stroke rehabilitation at a national rehabilitation hospital and examine long-term trends over a 10-year period using electronic medical record (EMR) data.Methods: This retrospective observational study analyzed EMR data from 3,069 adult patients with stroke admitted between January 2014 and December 2023. Among them, 1,751 patients who received at least one KM intervention during hospitalization were included in the primary analysis. Patient characteristics, length of stay, functional status (K-MBI), cognitive status (K-MMSE), timing of KM initiation, treatment duration, treatment modalities, frequency, and annual KM collaboration rates were analyzed using descriptive statistics.Results: The mean age of patients who received KM was 61.1 ± 13.6 years, and 62.2% were male. The mean hospital stay was 109.3 ± 37.6 days. At admission, mean K-MBI and K-MMSE scores were 49.9 ± 25.7 and 20.8 ± 9.2, respectively. KM was initiated an average of 38.8 ± 24.2 days after admission and was provided for 59.0 ± 32.1 days on average. Acupuncture (98.2%) and Korean medicine physical therapy (98.1%) were the most frequently administered modalities, whereas cupping (39.5%), moxibustion (34.8%), and herbal medicine (0.5%) were used selectively. The overall collaboration rate was 36.3%, and the utilization patterns remained relatively stable over time.Conclusions: In a collaborative inpatient rehabilitation setting, KM was selectively incorporated into stroke rehabilitation, primarily involving acupuncture and Korean medicine physical therapy. These findings describe the patterns of KM utilization in inpatient stroke care.